Blood Pressure and Cognitive Decline Over 8 Years in Middle-Aged and Older Black and White Americans. Issue 2 (February 2019) - Levine, Deborah A.; Galecki, Andrzej T.; Langa, Kenneth M.; Unverzagt, Frederick W.; Kabeto, Mohammed U.; Giordani, Bruno; Cushman, Mary; McClure, Leslie A.; Safford, Monika M.; Wadley, Virginia G.
Abstract : Although the association between high blood pressure (BP), particularly in midlife, and late-life dementia is known, less is known about variations by race and sex. In a prospective national study of 22 164 blacks and whites ≥45 years without baseline cognitive impairment or stroke from the REGARDS cohort study (Reasons for Geographic and Racial Differences in Stroke), enrolled 2003 to 2007 and followed through September 2015, we measured changes in cognition associated with baseline systolic and diastolic BP (SBP and DBP), as well as pulse pressure (PP) and mean arterial pressure, and we tested whether age, race, and sex modified the effects. Outcomes were global cognition (Six-Item Screener; primary outcome), new learning (Word List Learning), verbal memory (Word List Delayed Recall), and executive function (Animal Fluency Test). Median follow-up was 8.1 years. Significantly faster declines in global cognition were associated with higher SBP, lower DBP, and higher PP with increasing age ( P <0.001 for age×SBP×follow-up-time, age×DBP×follow-up-time, and age×PP×follow-up-time interaction). Declines in global cognition were not associated with mean arterial pressure after adjusting for PP. Blacks, compared with whites, had faster declines in global cognition associated with SBP ( P =0.02) and mean arterial pressure ( P =0.04). Men, compared with women, had faster declines in new learning associated with SBP ( P =0.04). BP was not associated with decline of verbal memory and executive function, after controlling for the effect of age on cognitive trajectories. Significantly faster declines in global cognition over 8 years were associated with higher SBP, lower DBP, and higher PP with increasing age. SBP-related cognitive declines were greater in blacks and men. Abstract : Supplemental Digital Content is available in the text.